Design of a Payroll Information System Using Zachman Framework for Outsourcing Company - Faisyal Ali (International Journal of Information Systems and Technology, 2026)
PT. Bhakti Karya Cemerlang is an enterprise specializing in providing outsourcing services. As of July 2017, the company managed approximately 700 outsourced employees. The management of personnel data, partner contracts, and payroll calculations currently relies on Microsoft Office, which often results in operational inefficiencies, slow reporting, and high vulnerability to errors during employee evaluations. To mitigate these issues, this study develops a payroll information system utilizing the Zachman Framework. The framework systematically maps the enterprise architecture across four key perspectives: Planner, Owner/Analyst, Designer, and Builder. The final deliverable of this research is a web-based payroll system prototype. System testing was conducted using Black-Box testing with 68 test cases, yielding a 100% validity rate. Compatibility testing via SortSite software identified two critical issues, specifically due to the inactivation of Secure Sockets Layer (SSL) during the test environment. Evaluation of the enterprise architecture using the Enterprise Architecture (EA) Scorecard showed a success rate of 77.60%, validating the model's structure.